Caregiver burden, coping and social support in parents of children with cancer - Villegas Chavez, Mariela; Cassaretto Bardales, Mónica (Psicooncología, 2024)
Aim: To analyze the relationship between coping strategies, social support, characteristics of migrant parent caregivers and their children with cancer on caregiver overload of such parents. Zarit Burden Interview (Zarit et al., 1980), the COPE Inventory (Carver et al., 1989) and the MOS Social Support Questionnaire (Sherbourne y Stewart, 1991) were used. Method: Eighty-two caregivers (67 mothers and 15 fathers) residing in shelters for children with cancer and their caregivers, who migrated to the city to receive treatment, participated in this study. Results: Two regression models were performed to evaluate the impact of demographic and psychological variables on caregiver burden, the first model involves the global social support scale (R2 adjusted=.43, F=9.73, p
Keywords: Caregiver burden; coping strategies; social support; cancer